Processos de medicalização das infâncias : cartografias em um centro municipal de educação infantil - Oliveira, Tiago Nascimento de (2024)
This research, proposed to the Professional Graduate Program in Education at UFES, examines the medicalization processes of children who are the target audience of special education in a Municipal Early Childhood Education Center (CMEI) in the municipality of Serra, Espírito Santo, Brazil. Adopting a qualitative approach, the study combines case study and cartography as its primary methodologies. Semi-structured interviews were conducted with parents, teachers, and pedagogues, along with field observations and analysis of relevant documents. The theoretical framework is grounded in the concepts of biopower and medicalization, as proposed by Michel Foucault, Ivan Illich (with the concept of medical colonization), and Moysés and Collares, who contribute insights on medicalization. The research seeks to understand how the medical diagnosis process, influenced by the Diagnostic and Statistical Manual of Mental Disorders, 5th Edition (DSM-5) and the International Classification of Diseases (ICD-11), operates. The findings indicate that medical reports function as mechanisms for controlling and regulating children’s bodies, reinforcing the medicalization of behaviors that, in other contexts, could be considered normal. The dissertation offers a critical reflection on these practices. As an academic product, a YouTube channel titled “Childhood Cartographies: Inclusion and Medicalization” and three e-books were developed. One of these, The Adventures of Miguel, comprises three stories aimed at discussing the medicalization processes in childhood and the inclusion of children who are the target audience of special education